Effectiveness of topical application of an abacterial medium with a 25% dimethyl sulfoxide solution in the treatment of purulent hand diseases (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Based on the objectives of the study, the next stage of the work was aimed at studying the effect of the local abacterial environment on the healing process of purulent wounds of the hand. For this purpose, an abacterial medium with диметилсульфоксидаa 25% dimethyl sulfoxide solution was used, the method of which is described in detail in chapter II of the paper. The obtained results of the conducted studies make it possible to recommend the widespread use of a local abacterial medium with a 25% dimethyl sulfoxide solution in the treatment of purulent inflammatory surgical diseases of the fingers and hand in outpatient settings according to the developed method.